Evaluation of Mitotic Activity of Bone Marrow Under Short-Term Hypothermia - Aminov , Ruslan; Frolov, Оleksandr; Aminova, Alina; Makyeyeva , Lyudmyla (Problems of Cryobiology and Cryomedicine, 2022)
In this research, we have studied the mitotic activity of bone marrow when applying medicinal leeches and short-term hypothermia. The bone marrow mitotic indices were compared within an immediate examination of the thigh removed from the body and during a short-term hypothermia. As a result, no statistical differences were found between the mitotic levels during immediate examination and a short-term hypothermia in the intact animals and those after medicinal leech application, that evidenced to a hypothermal fixation of initial level of this index, preservation of biomembrane physiological state prior to hypotonic stress and cell morphology. The used here short-term hypothermia on bone marrow cells may be included in the multi-profile algorithm of laboratory analysis when studying a mitotic index in actively proliferating cells. Probl Cryobiol Cryomed 2022; 32(2):081–091